2022
DOI: 10.18585/inabj.v14i1.1759
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and TGF-β Contributes in Recurrent Otorrhea of Active Mucosal Chronic Otitis Media

Abstract: BACKGROUND: Active mucosal chronic otitis media (COM) is prevalent in lower-income countries and is associated with recurrent episodes of otorrhea due to chronic inflammation of the middle ear. Cytokines, which are well-known for their effects on the immune system, play an important role in the inflammatory response and tissue remodeling. The specific contributions of proinflammatory and immunoregulatory cytokines in the pathophysiology of active mucosal COM remain unclear. This study aimed to compare the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…(36,37) In addition, increased levels of TNF-a also play a role in the pathophysiology of other diseases that increase the inflammatory process. (38,39) We found that, in contrast to a-defensins protein expression which was decreased, IL-1b protein expression was increased during the study and the increase was significant at the end of the study as compared to that of normal-control rats. This indicates that the inflammatory process in HAEC will continue as a result of a decrease in the protein expression of a-defensins, the antimicrobial peptide.…”
Section: Discussionmentioning
confidence: 74%
“…(36,37) In addition, increased levels of TNF-a also play a role in the pathophysiology of other diseases that increase the inflammatory process. (38,39) We found that, in contrast to a-defensins protein expression which was decreased, IL-1b protein expression was increased during the study and the increase was significant at the end of the study as compared to that of normal-control rats. This indicates that the inflammatory process in HAEC will continue as a result of a decrease in the protein expression of a-defensins, the antimicrobial peptide.…”
Section: Discussionmentioning
confidence: 74%
“…(17) This is in line with the study on TNF-α which are proinflammatory and immune regulatory cytokines, may contribute to the pathogenesis of recurrent inflammatory in an otitis media suppurative chronic. (18) In our study there was a significant difference between the average levels of TNF-α in the treatment group and the control group. So, it is postulated that the administration The level of p53 in the treatment group was higher than in the control group.…”
Section: Discussionmentioning
confidence: 42%
“…Papers with different topics, and 1 paper for which data related to chronic otitis media could not be extracted. Finally, eight papers were included in our meta-analysis [20][21][22][23][24][25][26][27][28][29]. The literature screening process is shown in Figure 1.…”
Section: The Results and General Characteristics Of The Included Lite...mentioning
confidence: 99%